INFLUENCE OF SERVICE QUALITY, BRAND IMAGE, AND PRICE ON CUSTOMER SATISFACTION - Mila Karmila; Rita Tri Yusnita; Barin Barlian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research was conducted with the intention of analyzing the influence of several independent variables including brand image, service quality and price perceptions on the dependent variable, namely satisfaction. The objects in this study are customers from food distributor companies in Tasikmalaya City. The research method used in this study is multiple linear regression analysis and data obtained through observation, questionnaires and literature studies. The population in this research is 256 customers. The results showed that brand image, service quality and price perceptions had a positive effect on customer satisfaction either partially or simultaneously Keywords: Brand Image, Service Quality, Price and Customer Satisfaction